Professionalism and Interpersonal Skills for the Senior Medical Student Entering Surgery - Mara Antonoff; Courtney Green; Jennifer Swanson; Jonathan D'Chuna (Association of American Medical Colleges, 2014)
Abstract Introduction This resource includes comprehensive materials intended to provide senior medical students entering surgery specialties with the tools necessary to develop professionalism and interpersonal skills. Special attention was directed toward structuring the objectives of this resource on a foundation of the core competencies as defined by the ACGME. These objectives were further refined and expanded on review of proposed guidelines outlining educational objectives for trainees in their first year of surgical residency, as well as the published experiences of outside institutions. Methods Included in this resource are all necessary instructor's blueprints, PowerPoint presentations, and handouts for six sessions covering topics related to professionalism and interpersonal skills. These topics include: self-directed learning, ethics, finances, stress and anxiety, communication, and professionalism. A seventh and final session features a multiple-choice knowledge test on professionalism and interpersonal skills. Results The outcomes from this course have been extensively studied. We found that course participants demonstrated marked improvement and task-specific confidence in all tasks from course beginning to end. This was supported by improved scores on written and technical skill examinations. Furthermore, course participants outperformed peers in all tasks one month into internship, with their performance advantage predictably dissipating into the third month of residency. We found that competency-based preparation for surgical internship utilizing the tools found within this resource resulted in objective gains in task-specific confidence and test performance at course conclusion which, importantly, translated to improved performance upon residency matriculation. Discussion This resource may be used by course directors for surgery PGY-1 preparatory classes/bootcamps, for independent study by individuals planning to matriculate into surgical residencies, or as a review source for those already in surgical training. While these materials were designed to meet the needs of new surgical house staff, the contents are easily generalized to other medical specialties, and would prove useful for any trainee managing hospital inpatients.